RANCANG BANGUN SUPERVISI SISTEM PENCEGAH DAN PEMADAM KEBAKARAN BERBASIS IOT - Sandy Bhawana Mulia; Nur Wisma Nugraha; Ilham Rafif Mochamad (Jurnal Teknologi Terapan, 2021)
Fire is a disaster that often occurs but can be prevented. Based on data from the Bandung City Central Bureau of Statistics (BPS), in 2018 there were 198 fire incidents (16.5 events / month), and in a periode 2012 - 2017 fires caused by LPG gas had the second largest percentage at 17%. Therefore a fire extinguishing system that can detect and prevent it quickly and can be monitored remotely in real time will help minimize losses. This system design uses an LM35 sensor which can detect temperature, the KY-026 sensor can detect the presence of hotspots in any room, and the MQ-6 sensor can detect the levels of LPG gas in the room. Moreover, this system design is also able to drive 2 emergency doors, pumps and exhaust fans according to the specified algorithm. The system interface can provide actuator information on the prototype as well as the location of the fire plan with a delay of each data change of 6.67 seconds. And the system is able to provide an indicator of the evacuation route during a fire.